Impact of a novel biomarker, T‐LAK cell‐originating protein kinase (TOPK) expression on outcome in malignant glioma. Issue 2 (21st December 2017) - Hayashi, Tomohide; Hayakawa, Yumiko; Koh, Masaki; Tomita, Takahiro; Nagai, Shoichi; Kashiwazaki, Daina; Sugimori, Michiya; Origasa, Hideki; Kuroda, Satoshi
Abstract : This study aimed to evaluate the biological features of T‐lymphokine‐activated killer cell‐originating protein kinase (TOPK) in vitro and to assess clinical impact of TOPK on the outcome in patients with malignant glioma. TOPK protein level and TOPK mRNA and protein levels in six glioma cell lines were examined using Western blot and reverse transcription‐polymerase chain reaction (RT‐PCR), respectively. Immunohistochemistry was performed to examine their subcellular localization of TOPK. Using surgical specimens from 57 patients with gliomas, TOPK and Ki‐67 expressions were examined by immunohistochemistry. Their co‐localization was also examined with double immunofluorescence immunohistochemistry. Impacts of TOPK/Ki‐67 expression on the overall survival (OS) and progression‐free survival (PFS) in 32 patients with glioblastoma multiforme (GBM) were examined, using Kaplan–Meier and Cox proportion hazard models. Immunohistochemistry revealed that approximately 20–30% of glioma cells were positive for TOPK in vitro. TOPK mRNA was identified in all glioma cell lines on RT‐PCR. The value of TOPK/GAPDH was 0.27 ± 0.11. TOPK and Ki‐67 expressions were significantly higher in GBM patients than in non‐GBM patients. A majority of TOPK‐positive cells were also positive for Ki‐67 and vice versa . Multivariate analysis revealed that a low TOPK expression (≤ 12.7%) was an independent predictor of longer OS ( P  = 0.0372), and that gross total removal and a low TOPK expression (≤ 12.7%) were independent predictors of longer PFS ( P  = 0.0470 and P  = 0.0189, respectively). The findings strongly suggest biological and clinical importance of TOPK expression in gliomas, indicating a novel therapeutic potential of TOPK inhibitors to treat malignant gliomas.